Влияние пространственной симметрии реактора на типы осциллирующих структур в объеме при осцилляции граничного слоя реакционной зоны - Г. Н. Саргсян (ՀՀ ԳԱԱ հրատ.)
Рассмотрено влияние пространственной симметрии реакционного сосуда на развитие осцилляционного цепного процесса окисления органических соединений. Исследуются случаи, когда осцилляции вызываются взаимодействием поверхностных и объемных процессов, приводящих к установлению осцилляционного граничного слоя. Դիտարկվում է ռեակտորի տարածական սիմետրիայի ազդեցությունը օրգանական նյութերի օքսիդացման շղթայական պրոցեսի զարգացման վրա, եթե այդ համակարգում սահմանային շերտում առաջանում են կոնցենտրացիոն տատանումներ` պայմանավորված ծավալային և մակերևութային պրոցեսների փոխազդեցությամբ: Մաթեմատիկական դիտարկումները հիմնված են ացետալդեհիդի ցածր ջերմաստիճանային իզոթերմիկ օքսիդացման մոդելի վրա: Influence of dimensional symmetry of a reaction vessel on development of oscillation chain process of an oxidation of organic compounds for a case when oscillations are called by interaction of the surface and volumetric processes, resulting in to installation of oscillation boundary layer. The opportunity of formation of concentration oscillations localized in boundary layer, at chain reactions, becomes possible if inhibitor of process the excited molecule is formatted at heterogeneous recombination. Owing to rather small a lifetime in comparison with stable particles, inhibitor does not make penetrate into a depth of reaction zone and their activities are localized at a surface of a reaction vessel.
Keywords: Physical Chemistry